Pengaruh Penggunaan Teknologi Informasi (Gadget) Terhadap Kesehatan Mental Peserta Didik di SMAN 18 Palembang - Putra, M. Defry Ananda; Habibullah, M. Sultan; Razzaq, Abdur; Nugraha, Muhamad Yudistira (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This research aims to analyze the influence of information technology usage, particularly gadgets, on the mental health of students at SMAN 18 Palembang. The massive use of gadgets among adolescents can have both positive and negative impacts on various aspects of life, including mental health. This study employs a quantitative method with a survey approach. Data was collected through questionnaires distributed to active students of SMAN 18 Palembang. Data analysis was conducted using descriptive and inferential statistical techniques to examine the relationship between the intensity of gadget use and mental health indicators such as stress levels, anxiety, depression, and sleep quality. The results of this research are expected to provide a clear picture of the extent to which gadget use correlates with the mental health conditions of students in this school environment. The implications of this study are expected to provide input for the school, parents, and students in an effort to minimize negative impacts and optimize the healthy and wise use of information technology for the mental well-being of the younger generation.